2017
DOI: 10.1093/nar/gkx1268
|View full text |Cite
|
Sign up to set email alerts
|

Refined sgRNA efficacy prediction improves large- and small-scale CRISPR–Cas9 applications

Abstract: Genome editing with the CRISPR–Cas9 system has enabled unprecedented efficacy for reverse genetics and gene correction approaches. While off-target effects have been successfully tackled, the effort to eliminate variability in sgRNA efficacies—which affect experimental sensitivity—is in its infancy. To address this issue, studies have analyzed the molecular features of highly active sgRNAs, but independent cross-validation is lacking. Utilizing fluorescent reporter knock-out assays with verification at selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
207
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(217 citation statements)
references
References 48 publications
10
207
0
Order By: Relevance
“…Using Drosophila as an experimental system, Ren et al () showed that a GC content of over 50% is beneficial only within the six nucleobases positioned immediately upstream of the PAM. Then again, Labuhn et al () reported a significant effect of the GC content in the domain comprising positions ‐8 through to −17 upstream of the PAM in human cells.…”
Section: Selection Of Target Motifsmentioning
confidence: 97%
“…Using Drosophila as an experimental system, Ren et al () showed that a GC content of over 50% is beneficial only within the six nucleobases positioned immediately upstream of the PAM. Then again, Labuhn et al () reported a significant effect of the GC content in the domain comprising positions ‐8 through to −17 upstream of the PAM in human cells.…”
Section: Selection Of Target Motifsmentioning
confidence: 97%
“…These tools are designed to assist researchers in the selection of best target sites by helping them exclude undesirable targets based on predicted low efficiency or a high potential for off-target effects. They could be broadly divided into two groups, on-target cleavage efficiency tools (6,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and off-target activity tools (18,28,33,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). In the on-target cleavage efficiency evaluation tools, researchers focus on identifying the gRNA sequence features that contribute to target cleavage efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR-Cas, a prokaryotic adaptive immune system, has been harnessed for genome editing in various species and cell types, including human cells [1][2][3][4][5][6] . The ability to accurately predict SpCas9 activity is important for applications of genome editing [7][8][9][10][11][12] . So far, several computational models that predict SpCas9 activity have been developed based on data sets of phenotypic changes of gene-edited cells 7,9,[11][12][13][14][15][16][17] or medium-sized data sets of SpCas9-induced indel frequencies obtained by episomal plasmid-based library-on-library approaches 10,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…The ability to accurately predict SpCas9 activity is important for applications of genome editing [7][8][9][10][11][12] . So far, several computational models that predict SpCas9 activity have been developed based on data sets of phenotypic changes of gene-edited cells 7,9,[11][12][13][14][15][16][17] or medium-sized data sets of SpCas9-induced indel frequencies obtained by episomal plasmid-based library-on-library approaches 10,18,19 . However, the generalization performances of these models have been limited 20 , possibly because the quality and size of the training data sets were not ideal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation